2023
DOI: 10.1101/2023.07.12.548715
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Host obesity impacts genetic variation in influenza A viral populations

Abstract: Obesity is a chronic health condition characterized by excess adiposity leading to a systemic increase in inflammation and dysregulation of metabolic hormones and immune cell populations. Obesity is well established as a risk factor for many noncommunicable diseases; however, its consequences for infectious disease are poorly understood. Influenza A virus (IAV) is a highly infectious pathogen responsible for seasonal and pandemic influenza. Host risk factors, including compromised immunity and pre-existing hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
0
0
Order By: Relevance
“…When vaccinated, they were more likely to have other chronic conditions, particularly diabetes, cardiovascular disease, or chronic lung disease. 62 Similarly, among the pediatric population, Karachaliou et al recently demonstrated that obese children had significantly lower rates of influenza vaccination compared to the general pediatric population; by the age of 4, only 13.3% of obese children were vaccinated compared to 37% of the general population, and by the age of 10, only 2.9% of obese children were vaccinated compared to 40% of the general population. 66 For these reasons, it is important to study the determinants of vaccine uptake for each specific risk group, in order to better address each gap in vaccination coverage with a targeted and tailored approach.…”
Section: Suboptimal Coverage Of Influenza Vaccination Among Obese Pat...mentioning
confidence: 98%
See 1 more Smart Citation
“…When vaccinated, they were more likely to have other chronic conditions, particularly diabetes, cardiovascular disease, or chronic lung disease. 62 Similarly, among the pediatric population, Karachaliou et al recently demonstrated that obese children had significantly lower rates of influenza vaccination compared to the general pediatric population; by the age of 4, only 13.3% of obese children were vaccinated compared to 37% of the general population, and by the age of 10, only 2.9% of obese children were vaccinated compared to 40% of the general population. 66 For these reasons, it is important to study the determinants of vaccine uptake for each specific risk group, in order to better address each gap in vaccination coverage with a targeted and tailored approach.…”
Section: Suboptimal Coverage Of Influenza Vaccination Among Obese Pat...mentioning
confidence: 98%
“…61 Other recent research on avian variants of the influenza virus (H9N2) has identified increased positive selection on de novo mutations in obese murine subjects, resulting in a variety of non-synonymous changes. 62 The analysis of the efficacy of antiviral treatment revealed that the use of oseltamivir did not positively impact virus clearance in obese mice, and no resistance mutations were identified. However, it led to phenotypic resistance in vitro.…”
Section: Dovepressmentioning
confidence: 99%